PRACTICAL ASPECTS OF ORGANIZING NUTRITION BASED ON CHILDREN'S AGE CHARACTERISTICS - Kamila, Saydullaeva (Recent scientific discoveries and methodological research, 2024)
Paying attention to children’s age characteristics in organizing their nutrition is one of the critical factors in ensuring healthy development. Age-appropriate nutrition not only meets children’s physiological needs but also supports their physical, mental, and emotional growth. In practice, this process is organized based on the biological compatibility of the diet, meal schedules, and adherence to hygienic standards. Children's nutrition must be tailored to their age characteristics. At each stage of development, the quantity of nutrients required for the child’s physiological needs, physical activity, and cognitive potential varies. Research indicates that age-inappropriate nutrition can lead to the development of chronic diseases, weakened immunity, and difficulties in academic performance.